2021
DOI: 10.2147/dmso.s307633
|View full text |Cite
|
Sign up to set email alerts
|

Low TSH Levels Within Euthyroid Range Could Play a Negative Role on Bone Mineral Density in Postmenopausal Women with Type 2 Diabetes

Abstract: Objective: We aimed to evaluate the relationship between thyroid-stimulating hormone (TSH) and bone mineral density (BMD) in euthyroid type 2 diabetes (T2D). Methods: This retrospective analysis enrolled 439 T2D patients with normal thyroid function, including 226 males and 213 females. All the female patients were postmenopausal. Serum glycosylated hemoglobin A1c (HbA1c), TSH, free triiodothyronine (FT 3 ), and free thyroxine (FT 4 ) concentrations were analyzed. BMD of the lumbar spine (L 1 -L 4 ), femoral n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…According to one of our published studies, thyroid hormones and TSH may influence bone transformation in postmenopausal women. 40 This concept was also supported by multilinear regression analyses in this recent study, which found that the level of FT3 could predict the status of N-MID.…”
Section: Discussionmentioning
confidence: 55%
“…According to one of our published studies, thyroid hormones and TSH may influence bone transformation in postmenopausal women. 40 This concept was also supported by multilinear regression analyses in this recent study, which found that the level of FT3 could predict the status of N-MID.…”
Section: Discussionmentioning
confidence: 55%
“…[22][23][24] A retrospective study from Shanghai also showed that low-normal TSH levels were associated with decreased BMD at the femoral neck and hip joint in postmenopausal T2DM women. 14 However, their subjects had a higher BMI of over 25 kg/m 2 and an older age of over 65 in average. On the other hand, Hwangbo's team from Korea reported the negative correlation of high-normal free T4 and trabecular bone scores in postmenopausal women, and TSH levels were not related to trabecular bone scores in either gender.…”
Section: Discussionmentioning
confidence: 93%
“…A recent retrospective study from Shanghai including 226 male and 213 female subjects aged over 65 years old showed that low TSH levels within euthyroid range are associated with decreased BMD at the femoral neck and hip joint in postmenopausal T2DM women. 14 However, the impact of obesity on BMD was neglected in the analysis. Another prospective cohort study conducted in Brazil claimed that the thyroid hormone profile was not associated with variations in BMD and body composition after 1 year follow-up in euthyroid healthy women who were both normal weight and overweight.…”
Section: Introductionmentioning
confidence: 99%
“…However, this study was small enough to have this conclusion [ 21 ]. Also, a study demonstrated a significant difference in both FN and hip BMD between low and high TSH level groups [ 27 ]. On the other hand, one study identified a significant difference in TSH levels between osteoporosis and normal groups.…”
Section: Reviewmentioning
confidence: 99%